University in the 21st century - Geberth, Lisa-Marie; Woller, Lisa-Teresa (Unifying science, culture, and society, 2023)
"University has changed dramatically over the last decades. From the spirit of Humboldt, that science in itself is the greatest motivator to study and do research, we experience a shift towards neoliberalism. Studying became part of something one needs to do to compete on a competitive job market. Research gets more and more influenced by interests of those financing research funds. Digitalization changed the way people interact in a university setting. This book shows different views regarding university: from being a student, becoming an alumnus and then maybe a teacher, challenging views on grading and exams, to problematic patriarchal structures and problems with creating a new study program. Students, alumni, researcher, and lecturers were invited to join this volume and give unique insights into (post-) university life"--